Governance Kooperatif dalam Penanganan Buruh Migran Ilegal dan Implikasinya terhadap Ketahanan Wilayah Perbatasan di Kalimantan Barat - Anggita, Irva; Suswanta, Suswanta; Listiani, Endang Indri; Ahdarrijal, Yujitia (Universitas Gadjah Mada, 2024)
This study aims to look at the implications for resilience in the border areas of Indonesia and Malaysia, reviewed from the existence of migrant workers, with a case study in West Kalimantan Province. This study uses a qualitative descriptive method based on the results of primary and secondary data analysis, data is obtained through searches of government websites, news, and reputable journals. The data obtained is then analyzed and then described according to the circumstances found factually which are then drawn conclusions from the data. The results of the study show that the border relationship between West Kalimantan and Sarawak Malaysia has long been the focus of attention, both in terms of economy and security. Cross-border trade and close social ties between the peoples of the two regions support the local economy. The data shows fluctuations in the number of illegal migrant workers from 2019 to 2023. In 2019, Indonesia recorded the highest number with 5,824 illegal workers, while Malaysia recorded 1,428 illegal workers. This number decreased drastically in 2020 due to various factors, including the COVID-19 pandemic. Despite efforts to overcome this problem, it still faces various challenges, so strict law enforcement and international cooperation are urgently needed to reduce the number of illegal workers. Differences in remittance/goods remittance activities between migrant and non-migrant workers open up opportunities to improve inclusive financial services. Participation in investment remained low in both groups, indicating the need for training programs and incentives to improve the financial literacy of migrant workers. Governments and the private sector need to work together to provide access to financial services and better rights protections for migrant workers. This collaborative effort is expected to create a sustainable positive impact on migrant workers and the community as a whole. This study provides insight into the complexity of dealing with illegal migrant workers on the border of West Kalimantan and potential solutions through a cooperative governance approach.